Effects of acupuncture on improving sleep quality and the risk of emotional maladjustment of breast cancer patients: a systematic review and meta-analysis - Yang, Yi; Wang, Hong; Chen, Zai Zhao; Teng, Qi Rui (Frontiers in Oncology, 2025)
BackgroundAcupuncture is highly controversial in enhancing the quality of sleep and the risk of emotional maladjustment in breast cancer patients. Through a comprehensive meta-analytic approach, this study intends to investigate the effects of acupuncture on enhancing sleep quality and the risk of emotional maladjustment in patients diagnosed with breast carcinoma.MethodsSearch tactics aligned with Cochrane Collaboration recommendations. Systematic electronic searches were conducted in April 2025 across several data storage, including PubMed, Embase, Web of Science, the Cochrane Library, and Scopus. The reference lists of review essay were manually searched to refine potentially eligible studies. A pair of researchers independently performed a comprehensive literature review, conducted data extraction, and assessed the risk of bias. Outcome analysis included the quality of sleep and the risk of emotional maladjustment. For continuous measures, the pooled weighted mean difference (MD) and 95% confidence interval will be estimated. The meta-analysis was conducted using the Review Manager 5.3 and Stata 16.0 statistical software platforms.ResultA total of 11 studies involving 1116 participants were included. Statistically significant differences were found between acupuncture and control group in Pittsburgh Sleep Quality Index (PSQI) (MD = -1.38, 95%CI = -2.45 to -0.31), Insomnia Severity Index (ISI) (MD = -1.11, 95%CI = -3.68 to 1.45), Brief Fatigue Scale (BFI) score (MD = -2.30, 95%CI = -5.62 to -1.03). Acupuncture has been shown to Boost sleep quality and reducing the risk of emotional maladjustment. Specifically, it is manifested in: Hospital Anxiety and Depression Scale (HADS-A) (MD = -1.24, 95%CI = -2.41 to -0.35) and Hospital Anxiety and Depression Scale (HADS-D) (MD = -1.18, 95%CI = -2.15 to -0.20).ConclusionIn comparison to other standard treatment modalities, acupuncture exhibits a notable distinction in boosting the sleep quality and the risk of emotional maladjustment of breast cancer patients. However, Clinicians should exercise caution when applying these results, as the available evidence suffers from methodological biases and quality limitations.